Assessment of performance, emission and combustion characteristics of palm, jatropha and Calophyllum inophyllum biodiesel blends. (1st October 2016) - Monirul, I.M.; Masjuki, H.H.; Kalam, M.A.; Mosarof, M.H.; Zulkifli, N.W.M.; Teoh, Y.H.; How, H.G.
Highlights: All of biodiesel blends showed almost 7.5% higher BSFC than diesel fuel. Diesel produces higher BP and BTE compared to biodiesel blends. JB20 produced 7.49% and 14.90% lower CO and HC emissions compared to diesel. JB10 produced 31.79% lower amount of smoke opacity than diesel fuel. PB20 has lower emission and better engine performance than diesel fuel. Abstract: Biodiesel is an alternative diesel fuel that is produced from renewable resources. Energy studies conducted over the last two decades focused on solutions to problems of rising fossil fuel price, increasing dependency on foreign energy sources, and environmental concerns. Palm oil biodiesel is mostly used in Malaysia. Engine performance and emission tests were conducted with a single-cylinder diesel engine fueled with palm, jatropha and Calophyllum inophyllum biodiesel blends (PB10, PB20, JB10, JB20, CIB10, and CIB20) and then compared with diesel fuel at a full-load engine speed range of 1000–2400 rpm. The average brake specific fuel consumption increased from 7.96% to 10.15% while operating on 10%, and 20%, blends of palm, jatropha and C. inophyllum biodiesel. The average brake power for PB10 and PB20 were 9.31% and 12.93% lower respectively compared with that for diesel fuel. JB10 showed higher amount of brake specific fuel consumption than diesel and other biodiesel blends. PB20 produces comparatively lower CO and HC emissions than diesel and biodiesel blends. JB10 showed 31.09% lower smoke opacity than diesel fuel. Diesel produces lower amount of NO X emission compared to biodiesel blends. The higher peak cylinder pressure and heat release rate were found with CIB blends compared to diesel fuel, palm and jatropha biodiesel blends. Results indicated that PB20 has better engine performance, and lower emission compared with diesel and biodiesel blends. Thus, PB20 is suitable for use in diesel engines without the need for any engine modification.